2017
DOI: 10.1515/msp-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of nanostructured bismuth sulphide and Mn (II) doped bismuth sulphide nanoparticles: characterization and application

Abstract: Different morphologies of bismuth sulphide (Bi 2 S 3 ) nanoparticles (NPs) were synthesized at room temperature using wet chemical method. The properties of bismuth sulphide (Bi 2 S 3 ) nanoparticles can be controlled by different amounts of Mn 2+ dopant. The synthesized nanoparticles were characterized by several techniques, such as high resolution scanning electron microscopy (HR-SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), electron diffraction (ED), and energy dispersive X-ray spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Different transition metal-doped bismuth sulfide nanoparticles have been reported. Anasane and Ameta reported manganese (Mn 2+ ) doped Bi 2 S 3 nanoparticles of different morphologies [ 16 ]. A simple synthesis of Eu-doped Bi 2 S 3 nanoparticles, in various ratios, through the breakdown of dual single source precursors: Bi(III) dithiocarboxylate and Eu(III) dithiocarboxylate complexes has been described [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different transition metal-doped bismuth sulfide nanoparticles have been reported. Anasane and Ameta reported manganese (Mn 2+ ) doped Bi 2 S 3 nanoparticles of different morphologies [ 16 ]. A simple synthesis of Eu-doped Bi 2 S 3 nanoparticles, in various ratios, through the breakdown of dual single source precursors: Bi(III) dithiocarboxylate and Eu(III) dithiocarboxylate complexes has been described [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic decolorization of azo dye acid orange 7 (AO7) was investigated using as-synthesized powder under sunlight. Anasane and Ameta 18 reported morphologies of nanostructured bismuth sulphide and Mn (II) doped bismuth sulphide nanoparticles and decolorization of methyl violet using as prepared doped bismuth sulphide while Ashok et al 19 reported hydrothermal synthesis of ultraviolet-visible light responsive ruthenium doped titania (RuXTi1-XO2) nanosheet and also investigated its effect on photocatalytic degradation of reactive red dyes. In the present study, nanosized barium chromate has been prepared and it was further used to investigate the photocatalytic degradation of malachite green.…”
Section: Degradation Of Malachite Greenmentioning
confidence: 99%
“…The literature is replete with articles discussing the effects of doping on metallic chalcogenides. [13][14][15][16][17] Capped bismuth sulfide nanoparticles have been described in a number of studies. Tumours targeted albumin-coated bismuth sulfide, [18] silica-coated bismuth sulfide, [19] BSA-mediated synthesis of bismuth sulfide, [20] have been reported.…”
Section: Introductionmentioning
confidence: 99%